Catheter entrapment due to severe radial artery spasm during transradial approach - Zencirci, Ertugrul; Degirmencioglu, Aleks (VIA MEDICA, 2016)
Background: Catheter entrapment due to severe radial artery spasm (RAS) during transradial coronary catheterization has been rarely reported and its management is not precisely defined. The aim of this study was to determine the incidence, predictors and management of catheter entrapment due to severe RAS. Methods: A total of 723 patients undergoing transradial coronary catheterization at a single center were retrospectively enrolled in the present study. Patients were divided into two groups: those with catheter entrapment due to severe RAS and those without. Results: The incidence of catheter entrapment was 0.8\%. Height (161.2 +/- 9.1 cm vs. 169.6 +/- +/- 10 cm, p = 0.047) and body surface area (1.86 +/- 0.04 vs. 1.95 +/- 0.18, p = 0.002) were found to be lower, and total procedure time 33.2 +/- 13.4 min vs. 15.2 +/- 12.3 min, p < 0.001) was longer in the entrapment group. Multivariate logistic regression analysis demonstrated that total procedure time independently predicted catheter entrapment (odds ratio: 1.057, 95\% confidence interval {[}CI] 1.004-1.114, p = 0.035). Receiver-operating characteristic curve demonstrated good diagnostic accuracy for prolonged total procedure time in predicting catheter entrapment (area under curve = 0.8, 95\% CI 0.63-0.97, p = 0.01). Patients were effectively treated with stepwise administration of systemic vasodilators, forearm heating, sedation and as a last resort general anesthesia with no significant complication. Conclusions: Catheter entrapment due to severe RAS during transradial approach was rare and prolonged total procedure time is an independent predictor of catheter entrapment. Treatment with stepwise administration of different treatment modalities is possible with no significant complication.
Keywords: catheter entrapment; radial artery spasm; transradial approach